Prevalence of metabolic syndrome in hypothyroidism: Experience in a tertiary center in South India - Jaideep Khare; Smitha Nalla; Jyoti Wadhwa; Prachi Srivastava; Babul Reddy; Prasun Deb (Wolters Kluwer Medknow Publications, 2017)
Introduction: Thyroid disorders are among the most common endocrine disorders, with an overall prevalence of hypothyroidism about 10.95% in the general population. Prevalence of the metabolic syndrome (MetS) in the Indian population is about 31.6%, with the prevalence of 22.9% in men and 39.9% in women. Aim: The aim of this study is to determine the prevalence of MetS and its components in people with hypothyroidism. Materials and Methods: A total of 154 hypothyroid patients attending our outpatient department were consecutively enrolled for the study. MetS identified by National Cholesterol Education Program's Adult Treatment Panel III report (ATP III). Clinical data were obtained by interviewing the patients and referring to their case folders and prescriptions. The anthropometric indices were recorded. The laboratory parameters that were analyzed included fasting lipid profile, thyroid function tests, and fasting blood sugars. Results: The patients were aged between 18 and 75 years, with a mean age of 43.6 years, and the female-to-male ratio was 123:31. The overall prevalence of the MetS was 53.24% by ATP III criteria, which is significantly higher than that in the general population, as reported earlier in various studies. The most common occurring MetS-defining criterion was increased waist circumference, and hypertension was the least documented criterion. Conclusion: MetS occurs in approximately every second patient of hypothyroidism, and so, routine screening for components of MetS may be of benefit in this group.